Knowledge management infrastructure: Preliminary evidences of Malaysian banking practice - Hamidi, Meisam; Abd Aziz, Azira; Mat Sin, Nazirah; P., Woods (2012)
Knowledge Management (KM) has become a vital concept for Malaysian banking industries in enhancing their competitive advantage.Leveraging the power of knowledge occurs when individuals intended to share their knowledge.When there is a trust and secure feeling of ownership, the knowledge will spread without any constraints.With an adequate infrastructure in organizations, it can ease the communication and employees interaction for knowledge sharing. The purpose of this research is to investigate the impact of infrastructure, organizational culture, organizational structure and technology towards knowledge sharing in banking industries.